2018
DOI: 10.1007/s12307-018-0211-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: Definition, Role in Tumor Development and Clinical Implications

Abstract: Exosomes are microvesicles released by cells in both physiological and pathological situations. They are surrounded by a lipid bilayer with proteins derived from the origin cell, and contain a variety of molecules, such as nucleic acids. They represent an emerging mechanism of intercellular communication, and they play an important role in the pathogenesis of cancer, stimulating proliferation and aggressiveness of cancer cells, inducing a microenvironment favorable to tumor development and controlling immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 86 publications
(114 reference statements)
0
24
0
2
Order By: Relevance
“…Exosomes are extracellular vesicles secreted by cells; they exist in urine, plasma, lavage fluid, serous cavity effusion, cerebrospinal fluid and other body fluids ( 12 , 13 ). They have a lipid bilayer with a diameter of 30–150 nm, and their contents include DNA, RNA, protein and lipids ( 14 , 15 ). Exosomes are released through cells into the circulation and body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are extracellular vesicles secreted by cells; they exist in urine, plasma, lavage fluid, serous cavity effusion, cerebrospinal fluid and other body fluids ( 12 , 13 ). They have a lipid bilayer with a diameter of 30–150 nm, and their contents include DNA, RNA, protein and lipids ( 14 , 15 ). Exosomes are released through cells into the circulation and body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, liquid biopsy could represent the new era for biomarkers detection: the term “liquid biopsy” refers to the isolation of cancer-derived components, such as circulating tumor cells (CTC), circulating tumor DNA (ctDNA), microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and proteins, from peripheral blood or other body fluids (i.e., ascites, urine, pleural effusion, and cerebrospinal fluid), and their genomic or proteomic assessment [ 15 , 16 ]. Furthermore, exosomes (EXOs) which are membrane-bound extracellular vesicles containing proteins and nucleic acids released in the bloodstream by cancer cells, could represent potential biomarkers [ 17 , 18 ]. The aim of this review was to summarize the current knowledge of the role of liquid biopsy in the management of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that exosomes also play an important role in regulatory signaling of bone remodeling process. “Exosomes are defined as cell-derived vesicles formed from invagination of the cell membrane released to the extracellular space against different stimuli” (Carretero-González et al, 2018 ). Exosomes are small vesicles of 40–100 nm in size that were identified to play the role of signaling mediators in intra-cellular communications.…”
Section: Introductionmentioning
confidence: 99%